Cranial dural permeability of inflammatory nociceptive mediators: Potential implications for animal models of migraine. (October 2017) - Zhao, Jun; Bree, Dara; Harrington, Michael G; Strassman, Andrew M; Levy, Dan
Background: Application of inflammatory mediators to the cranial dura has been used as a method to activate and sensitize neurons in the meningeal sensory pathway in preclinical behavioral studies of headache mechanisms. However, the relatively high concentrations and volumes used in these studies raise the question of whether the applied agents might pass through the dura to act directly on central neurons, thus bypassing the dural afferent pathway. Methods: We used a radiolabeling approach to quantify the meningeal permeability of two of the inflammatory mediators, 5-HT and PGE2, when applied to the cranial dura as part of an inflammatory mixture used in preclinical headache models. Results: Both agents could be detected in samples taken four hours after dural application in the cerebrospinal fluid (CSF) and, in measurements made only for PGE2, in the central nervous system (CNS) as well. Based on our measurements, we made estimates of the CSF and CNS levels that would be attained with the higher concentrations and volumes of 5HT and PGE2 that were exogenously applied in previous pre-clinical headache studies. These estimated levels were comparable to or larger than normal endogenous levels, potentially large enough to have physiological effects. Conclusions: The finding that the cranial meninges are permeable to the two tested inflammatory mediators PGE2 and 5-HT raises some uncertainty about whether the behavioral changes observed in prior pre-clinical headache studies with these as well as other agents can be attributed entirely to the activation of dural nociceptors, particularly when the agents are applied at concentrations several orders of magnitude above physiological levels.